US Nuclear Posture Review 2018: Unwisely Re-opening 'Settled' Nuclear Issues. (September 2018) - Sethi, Manpreet
The latest NPR released in 2018 under the watch of President Trump, unabashedly echoes the sentiment of America First. Many nuclear war-fighting issues and concepts that had been settled in the past after having been experimented with and discarded for the risks they carried have yet again been adopted by the current NPR. But, America's sole focus on its own security alone could end up creating more security dilemmas for the US, and others. This article identifies the main highlights of the NPR, as well as its limitations, and the implications of both for nuclear strategies of major nuclear players. It describes and analyses the context, the content and the consequences of the NPR. It specifically flags some issues/actions that India must particularly watch out for since some of these need to be monitored for their implications on the nuclear strategies and trajectories of India's nuclear armed neighbours.